Analysis of NFAT-regulated gene expression in vivo: a novel perspective for optimal individualized doses of calcineurin inhibitors - Giese, Thomas; Zeier, Martin; Meuer, Stefan (Nephrology, dialysis, transplantation, 2004)
BACKGROUND: With the introduction of cyclosporine A (CsA) long-term allograft function has been significantly improved. Problems regarding limited therapeutic margins and CsA toxicity remain unsolved. Up to now there are no reliable, practical markers to measure the biological activity of CsA in vivo. METHODS: Expression of nuclear factor of activated T lymphocytes (NFAT)-regulated genes in PMA/ionomycin-stimulated peripheral blood from stable renal-transplant (n = 25) recipients under CsA therapy were measured by quantitative real-time RT-PCR before and 2 h after drug intake. The relative expression of three NFAT-regulated genes was scored, averaged and presented as the multi-gene expression score ranging from 0 to 12 points. Gene expression data and CsA plasma levels were correlated. RESULTS: A reliable and precise method to measure functional consequences of calcineurin inhibition in the individual patient was established. The individual decline in NFAT-regulated gene expression and the total drug exposure were in close relation (rho = 0.602). CONCLUSION: Quantitative measurement of NFAT-regulated gene expression in CsA-treated patients represents a potent new approach to assess the biological effectiveness of CsA therapy and has the potential to enable individualized immunosuppressive regimens.